Principle of self-defence and surgical sterilization - Fernandez Sanchez, Francisco Cristobal (Medicina e Morale, 1994)
The author argues the problem of the surgical sterilization of mentally sick (MS) as a preventive measure of the rape an d its consequencies. The article distinguish the concepts of contraceptive sterilization (CS) and therapeutic sterilization (TS). These two surgical procedures are quite different from the ethical pont of view, according the personalistic mode!. Indeed, the aim of CS is the destruction or the obstruction of the reprodllctive function, and for this reason it is never ethically justifiable. Instead, TS attaches a practical aim to the recovery of health (then therapeutic), even though produces the (permanent or temporary) destruction of the reproductive function. So, TS may be ethically justifiable. The author claims that drop in attention to ontological structure of the person's choices conducts to a biological concept of the contraception, that impedes the understanding of the objective, intrinsic unethicality of the choice of CS. So, the lacking of informed consent by MS - to order CS for this kind of patient- cannot be supplied by a positive law. Neither therapeutic principle nor principle of self-defence cannot justify CS for MS.